Level of corporate social disclosure in Malaysia / Hasnah Haron … [et al.] - Haron, Hasnah; Yahya, Sofri; Manasseh, Sharon; Ismail, Ishak (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
The research examines the level of corporate social disclosure among Bursa Malaysia listed companies during the period of recession of financial crisis and also during the pre and post financial crisis periods. The level of disclosure is measured using content analysis. The sample of 135 companies analysed included companies that existed from 1996 and remained going concerns until the year 2000. The disclosures on corporate social responsibility were found primarily in chairman's' reports. Our results show that the highest level of disclosure was in 1998, that is the period just after the economic crisis period. The human resource theme was the most disclosed item. Disclosures were mainly qualitative and favourable in nature.